2019
DOI: 10.1021/acs.orglett.9b00074
|View full text |Cite
|
Sign up to set email alerts
|

Single C(sp3)–F Bond Activation in a CF3 Group: Ipso-Defluorooxylation of (Trifluoromethyl)alkenes with Oximes

Abstract: The first defluorinative ipso-functionalization reaction of (trifluoromethyl)alkenes is reported. This exclusively regioselective ipsodefluorooxylation of (trifluoromethyl)alkenes with oximes affords various attractive O-(1,1-difluoroallyl)oxime ethers efficiently via a chemoselective single C(sp 3 )−F bond activation in the CF 3 group. Primary mechanism studies indicated an anionic S N 2-type substitution pathway might be involved in this transformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 70 publications
(25 reference statements)
2
29
0
Order By: Relevance
“…In 2019, Zhu and Jiang developed an unprecedented base‐mediated regioselective ipso ‐defluorooxylation of trifluoromethylalkenes 245 with oximes 244 , giving a number of O ‐(1,1‐difluoroallyl)oxime ethers 246 in moderate to high yield under transition‐metal‐free conditions (Scheme 64). [91] Preliminary mechanistic investigations indicated that an anionic S N 2‐type substitution process might be involved in this transformation. Additionally, further synthetic applications, for example, hydrogenation, oxidation, and cycloaddition, were also explored.…”
Section: Defluorinative Functionalization Of Trifluoromethylalkenesmentioning
confidence: 99%
“…In 2019, Zhu and Jiang developed an unprecedented base‐mediated regioselective ipso ‐defluorooxylation of trifluoromethylalkenes 245 with oximes 244 , giving a number of O ‐(1,1‐difluoroallyl)oxime ethers 246 in moderate to high yield under transition‐metal‐free conditions (Scheme 64). [91] Preliminary mechanistic investigations indicated that an anionic S N 2‐type substitution process might be involved in this transformation. Additionally, further synthetic applications, for example, hydrogenation, oxidation, and cycloaddition, were also explored.…”
Section: Defluorinative Functionalization Of Trifluoromethylalkenesmentioning
confidence: 99%
“…While effective, these stepwise protocols are unideal from the viewpoint of practicality and step‐economy, thus leaving ample room for the development of more efficient strategy for the α‐selective C−F bond functionalization of alkenyl‐CF 3 . It should be pointed out that an interesting S N 2 type selective defluorinative oxylation of alkenyl‐CF 3 was disclosed by Zhu and Jiang's group, although the competent nucleophile was limited to oxime [17] . Herein, we report a strategically novel protocol for α‐selective C−F bond allylation of trifluoromethylalkenes using allylsilane as both allyl donor and fluoride scavenger under thermal reaction conditions (Scheme 1 c).…”
Section: Methodsmentioning
confidence: 98%
“…It should be pointed out that an interesting S N 2 type selective defluorinative oxylation of alkenyl-CF 3 was disclosed by Zhu and Jiangs group, although the competent nucleophile was limited to oxime. [17] Herein, we report a strategically novel protocol for a-selective C À F bond allylation of trifluoromethylalkenes using allylsilane as both allyl donor and fluoride scavenger under thermal reaction conditions (Scheme 1 c). Several notable features of the present reaction need to be pointed out: 1) a cascade of S N 2' defluorinative allylation and Cope rearrangement enables challenging C À F bond functionalization; 2) a self-sustained silane activation is achieved with the extruded fluoride; 3) fluorine substituents prompt a selective 3,3rearrangement and such effect is attenuated with the reduction of fluorine substitution; 4) the selectivity for mono-CÀF Scheme 1.…”
mentioning
confidence: 99%
“…The protocol is remarkably general, and only alkyl fluorides reacted chemoselectively in the presence of other halides. Zhu and Jiang's group [204] developed a defluorinative ipso-functionalization reaction of (trifluoromethyl)alkenes with oximes through an anionic S N 2-type substitution pathway (Scheme 81). Under the base conditions, various O-(1,1difluoroallyl)oxime ethers (456−461) were synthesized.…”
Section: ) Under Mild Conditionsmentioning
confidence: 99%